Comparison of Techniques for Preimplantation Treatment of Osteochondral Allograft Bone - Baumann, Charles A.; Baumann, John R.; Bozynski, Chantelle C.; Stoker, Aaron M.; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2019)
Articular defects are a major problem with few effective treatment options. Osteochondral allograft (OCA) transplantation can be an effective treatment; however, lack of OCA bone integration can cause failure. This controlled laboratory study was designed to compare clinically applicable methods for marrow element removal and enhanced delivery of bone marrow aspirate concentrate (BMC) to OCA bone. We hypothesized that compressed carbon dioxide (CO2) treatment of OCA bone would result in significantly better marrow element removal, significantly more retention and distribution of viable osteoprogenitor cells, and significantly higher osteoinductive protein elution from OCAs compared with other preimplantation treatments. Fresh humeral heads (n = 24) were harvested and stored for 14 days, then randomly assigned to treatment based on marrow element removal and bone treatment: (standard of care [SOC]) (n = 4) – SOC high-pulse saline lavage, no BMC; (BMC) (n = 5) – saline lavage then canine BMC; (Drill + BMC) (n = 5) – 1.1 mm drill-hole immediately subchondral then saline lavage then BMC injection through drill hole; (Carb + BMC) (n = 5) – saline lavage then CO2 then BMC; or (Saline-Carb + BMC) (n = 5) – saline lavage and CO2 together then BMC. Treated OCAs were cultured for 14 days. On day 3, media were collected, centrifuged to isolate cells, and replaced. Cells were cultured for 11 days for colony forming unit (CFU) determination. OCA media were collected on days 7 and 14 of culture for analysis. On day 14, each graft was assessed for viable cell retention and distribution, and bone marrow element removal. BMC had significantly higher (p = 0.001) viable cell distribution compared with the SOC, Drill + BMC, Carb + BMC, and Saline-Carb + BMC groups. BMC and Drill + BMC had significantly higher (p < 0.05) CFUs than SOC, Carb + BMC, and Saline-Carb + BMC. Drill + BMC and Carb + BMC had the highest media concentrations of the osteoinductive biomarkers. The Carb + BMC and Saline-Carb + BMC groups were associated with significantly superior marrow element removal (p < 0.02) compared with the SOC, Drill + BMC, and BMC groups. Saline irrigation plus saturation with autogenous BMC appears to be the most advantageous preimplantation treatment for OCA transplantation.
Keywords: osteochondral allograft; bone marrow aspirate concentrate; orthobiologics; bone marrow removal; transplantation